Traditions and Specifics of the Regional Culture of the Besarabian Lands of the Danube in the Context of European Paradigms - Bukhnieva, Olena; Wang Chenхі (Journal of Danubian Studies and Research, 2023)
The article is devoted to the consideration of some traditions and specifics of the regional musical culture of the Bessarabian lands of the Danube region, associated with the strengthening of European trends in Ukraine. This topic needs a multilateral study due to the reasons for the geopolitical transformations that are taking place in the 21st century. Previously, Bessarabia was part of the Russian Empire, so its social, economic and cultural ties with Romania were interrupted. Today, the Bessarabian lands belong to the Ukrainian state, so we can talk about the continuation and development of the cultural traditions of regional ethnic art in the difficult conditions of life in Ukrainian Bessarabia. We are talking about the preservation of the national traditions of musical art, accumulated before the beginning of the 21st century on the lands of Bessarabia and their development in the paradigm of a common European culture.